2010
DOI: 10.1108/00483481011017390
|View full text |Cite
|
Sign up to set email alerts
|

Are we doing the right thing?

Abstract: PurposeThis paper aims to advance the debate regarding the use of training evaluation tools, chiefly the Kirkpatrick model, in reaction to minimal use of the tools reported in the literature and the economic changes that have characterised the industrialised world in the past 20 years.Design/methodology/approachThe main argument – the need to design new evaluation tools – emerges from an extensive literature review of criticism of the Kirkpatrick model. The approach is deductive; the argument emerges from exta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 48 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…This research identified an increase in reaction over time. This is a fundamental finding as research has suggested that positive reactions can lead to effective learning (Giangreco, Carugati, & Sebatiano, 2010;Rajeev et al, 1996).…”
Section: Discussionmentioning
confidence: 92%
“…This research identified an increase in reaction over time. This is a fundamental finding as research has suggested that positive reactions can lead to effective learning (Giangreco, Carugati, & Sebatiano, 2010;Rajeev et al, 1996).…”
Section: Discussionmentioning
confidence: 92%
“…There are various theories or models which have been developed by scholars for evaluating training effectiveness. These include- However, among all these, Kirkpatrick's (1959) model continues to be the most preferred framework to evaluate training effectiveness, either by researchers or practitioners of its simple and practical approach (Holton, 1996;Leach & Liu, 2003;Kirkpatrick & Kirkpatrick, 2010;;Giangreco, et al 2010;Griffin, 2010) (Cited in Aziz, 2013; Dash, Das & Dash 2019). Kirkpatrick (1976) four stage model (See figure 02) include (1) trainee reactions (i.e., what trainees think of the training), (2) learning (i.e., what trainees learned) (3) behaviour (i.e., how trainees behaviour changes), and (4) organizational results (i.e.…”
Section: Measuring Training Effectivenessmentioning
confidence: 99%
“…The evaluation of all HRD initiatives is a crucial component of SHRD maturity as a critical element in enhancing its credibility, as well as being a mechanism to indicate the path of transforming training into HRD and accordingly to SHRD in organizations (Rao, 2014; Walton & Valentin, 2014). For HRD to become strategic, it should continuously demonstrate how its investments could pay off through the associated benefits for the organization, all stakeholder groups, and society (Giangreco, Carugati, & Sebastiano, 2010).…”
Section: Shrd Maturity At a Crossroads: Toward A Modified Cluster Ofmentioning
confidence: 99%